If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x*6x=12x
We move all terms to the left:
2x*6x-(12x)=0
We add all the numbers together, and all the variables
-12x+2x*6x=0
Wy multiply elements
12x^2-12x=0
a = 12; b = -12; c = 0;
Δ = b2-4ac
Δ = -122-4·12·0
Δ = 144
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{144}=12$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-12)-12}{2*12}=\frac{0}{24} =0 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-12)+12}{2*12}=\frac{24}{24} =1 $
| 10j+6=16 | | 4x+16=6(x-1) | | -35=b/6-38 | | 4x-8x-3=6-4x= | | 17x+9+21x-3+15x+15=180 | | 12+w=42 | | 46-v=250 | | 0,5+7x=12–2x | | 5x8=36+9x | | 1/3(x+2)=1/3x=2/3 | | 10x=30,x=3 | | 7+3c=64 | | 6(x-10)+2=4+2x | | 7x-38=70 | | .75x+80=6x+72 | | 2x2+4(x^2+3)-2=22 | | 5x+1=1-5x= | | 9v-9=45 | | -4(-2x=5)-5x=5=-24 | | F(0)=5x+2 | | 3x+57=20 | | .75+80=6x+72 | | F(6)=5x-7 | | x–8=24,x=32 | | 5k=6k−6 | | X(x+8)+1=62 | | 50.48=-22.02+4x | | 2(d-80)=20 | | -0.15p=-4.5 | | (6x/4)+3x=120 | | 2x+5+3x+2+2x-9=180 | | x+-121=262 |